2008
DOI: 10.1007/s00704-007-0372-7
|View full text |Cite
|
Sign up to set email alerts
|

Convective and stratiform rainfall and heating associated with the summer monsoon over the South China Sea based on TRMM data

Abstract: SummaryIn this study, we investigate the features of the convective and stratiform rainfall and latent heating associated with the summer monsoon over the South China Sea using TRMM data. Our findings are as follows. (1) Latent heating generated by the convective and stratiform heating algorithm (CSH), as well as convective and stratiform rainfall from satellite data can characterize the seasonal march of the South China Sea summer monsoon very well; (2) Analyses of both the CSH algorithm-estimated heating and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Several studies have pointed out a well-established connection between the South China Sea (SCS) region with the circulation and convection in the entire Asian monsoon region (Yasunari 1979;Webster et al 1998;Fukutomi and Yasunari 1999;Annamalai and Slingo 2001;Hoyos and Webster 2007). In addition, the seasonal march of the SCS monsoon has been well documented by LH and rainfall products from TRMM (Li et al 2009). Figure 10a shows the evolution of vertical LH profiles during the SCSMEX campaign from 5 May to 22 June 1998 using a moisture budget analysis from Johnson and Ciesielski (2002).…”
Section: South China Sea Monsoon Experimentmentioning
confidence: 96%
“…Several studies have pointed out a well-established connection between the South China Sea (SCS) region with the circulation and convection in the entire Asian monsoon region (Yasunari 1979;Webster et al 1998;Fukutomi and Yasunari 1999;Annamalai and Slingo 2001;Hoyos and Webster 2007). In addition, the seasonal march of the SCS monsoon has been well documented by LH and rainfall products from TRMM (Li et al 2009). Figure 10a shows the evolution of vertical LH profiles during the SCSMEX campaign from 5 May to 22 June 1998 using a moisture budget analysis from Johnson and Ciesielski (2002).…”
Section: South China Sea Monsoon Experimentmentioning
confidence: 96%
“…This led to major changes in the LH field and the circulation response to the LH was stronger than the other years. Li et al [98] and Wang and Huang [99] investigated the variation of the LH associated with the summer and the winter monsoon over the South China Sea (SCS). They found that the interannual variation of the LH over the SCS depended on El Nino or La Nina conditions, and the LH over the SCS was much smaller during El Nino years than during La Nina years.…”
Section: The Lh and The Climate Responsementioning
confidence: 99%